The Treatment of Depressed Chinese Americans Using Qigong in a Health Care Setting: A Pilot Study. (16th April 2013) - Yeung, Albert; Slipp, Lauren E.; Jacquart, Jolene; Fava, Maurizio; Denninger, John W.; Benson, Herbert; Fricchione, Gregory L.
Abstract : Background . This pilot study examined the feasibility and efficacy of providing Qigong treatment in a health center to Chinese Americans with major depressive disorder (MDD). Methods . Fourteen Chinese Americans with MDD were enrolled, and they received a 12-week Qigong intervention. The key outcome measurement was the 17-item Hamilton Rating Scale for Depression (HAM-D17 ); the Clinical Global Impressions-Severity (CGI-S) and -Improvement (CGI-I), the Quality of Life Enjoyment and Satisfaction Questionnaire, Short Form (Q-LES-Q-SF), and the Multidimensional Scale of Perceived Social Support (MSPSS) were also administered. Positive response was defined as a decrease of 50% or more on the HAM-D17, and remission was defined as HAM-D17 ≤ 7. Patients' outcome measurements were compared before and after the Qigong intervention. Results . Participants (N = 14 ) were 64% female, with a mean age of 53 (±14). A 71% of participants completed the intervention. The Qigong intervention resulted in a positive treatment-response rate of 60% and a remission rate of 40% and statistically significant improvement, as measured by the HAM-D17, CGI-S, CGI-I, Q-LES-Q-SF, and the family support subscale of the MSPSS. Conclusions . The Qigong intervention provided at a health care setting for the treatment of primary care patients with MDD is feasible. Further studies with larger sample sizes are warranted.